La réforme du Sénat canadien à la lumière d'expériences étrangères - Pelletier, Réjean (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1984)
It is generally recognized that the Canadian Senate has fared better in revising legislation than in representing regional interests. Any attempt to modify the Senate's role must take this fact into consideration. The author does precisely that in proposing that the seats should be realloted taking into account regional disparities, that Senators should be nominated by the provinces and, finally, that the Senate's powers should be reduced at a political level but increased to ensure proper representation of regional interests.